Socioeconomic status mediates racial differences seen using the AT(N) framework: Neuroimaging: Environmental and lifestyle factors. (7th December 2020) - Wisch, Julie; Hudson, Darrell; Coble, Dean W.; Xiong, Chengjie; Babulal, Ganesh M.; Gordon, Brian A.; Flores, Shaney E.; Dincer, Aylin; Benzinger, Tammie L.S.; Morris, John C.; Ances, Beau M.; Meeker, Karin L.
Abstract: Background: Previous research suggests that African Americans are potentially at greater risk for developing Alzheimer disease (AD). Genetic, social, environmental, and cardiovascular factors may increase the risk of AD. The objectives of this project are as follows: (1) Assess neuroimaging biomarkers of amyloid (A), tau (T), and neurodegeneration (N) for potential racial differences. (2) Consider mediating effects of socioeconomic status (SES) and cardiovascular risk factors on observed race differences. Methods: Imaging measures of AT(N) (amyloid and tau positron emission tomography (PET) structural magnetic resonance imaging, and resting state functional connectivity (rs‐fc)) were collected from African American (n=169) and Caucasian (n=935) participants. Cardiovascular (white matter hyperintensities on MRI, blood pressure, and body mass index) and area‐based socioeconomic status (SES) were assessed as possible mediating factors in a multiple mediation analysis. This analysis assumed nonlinear relationships between the mediation effects and allowed for all four mediators to be considered simultaneously. Results: Compared to Caucasian participants, African American participants had lower amyloid PET burden but greater neurodegeneration, as measured by decreased cortical volumes and decreased AD global rs‐fc signature. African American participants were substantially more likely to be female (64%) compared to Caucasian participants (55% female). Female participants had greater tau burden and decreased AD cortical signature volume; but no significant race by sex interactions were observed. African Americans had lower area‐based SES and higher blood pressure, BMI, and white matter hyperintensity volumes. These proposed mediators significantly influenced associations between race and cortical amyloid PET accumulation, AD cortical signature volume, and AD global rs‐fc signature. Area‐level SES in particular was a significant mediating factor, and BMI had a significant effect on amyloid burden. Conclusion: Observed racial differences in AD are not primarily due to immutable, genetic differences, but rather modifiable factors fueled by differences in social contexts and resources, particularly area‐level SES. Future studies should emphasize collection of relevant psychosocial factors in addition to the development of intentional diversity and inclusion efforts to improve the racial/ethnic and socioeconomic representativeness of AD studies.